North Banten Coastline Evolution Model (Case Study Tanara Beach Serang - Tanjung Kait Beach Tangerang) - Saharani, Reza Nurul; Subekti, Subekti; Priyambodho, Bambang Adhi; Wigati, Restu; Purnaditya, Ngakan Putu (Jurnal Fondasi, 2024)
Climate Central predicts that Banten's northern coastal land will disappear by 2030. Previously, Banten has lost more than 1 kilometer of its former land. The purpose of this research is to obtain a prediction model for the evolution of the coastline between Tanara Beach (Serang Regency) to Tanjung Kait Beach, Mauk (Tangerang Regency). The method used for this research is the One-Line Model method. Based on the coastline prediction model of segment 1, Tenjoayu progressed from 2025 to 2030. Shoreline retreat occurs significantly from 2020 to 2030 around Pedaleman. The modeled shoreline around Pedaleman to the western part of Cup Island progressed significantly from 2022- 2030. The shoreline in segment 2, East of Cup Island, progressed from 2025 to 2030. West of the Ci Manceuri Estuary, the coastline retreats significantly from 2022 to 2030. East of the Ci Manceuri Estuary, the coastline tends to stabilize. Around Tanjung Kait Beach, the shoreline pattern advances significantly each year from 2022 to 2030.